1995
DOI: 10.1111/j.1432-1033.1995.0681p.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding Properties and Protease Stability of Recombinant Human Nidogen

Abstract: Recombinant human nidogen was obtained from transfected kidney cell clones as a 150-kDa protein with a three-globule structure. It was modified by sulfation and 0-glycosylation and a lower level of Nglycosylation than mouse nidogen. Recombinant nidogens of both species were, however, indistinguishable in their affinities for laminin-1 and a recombinant laminin y l chain fragment and showed a similar binding to collagen IV and the heparan sulfate proteoglycan perlecan. The two nidogens were also equivalent in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…The half-maximal reactions occurred around 1–2 nM nid-1, in agreement with the apparent dissociation constant, Kd [34]. Previous studies showed that human nid-1 had weaker affinities for collagen IV and perlecan than for laminin [11]. We next examined the binding of a mixture of nid-1 fragments produced by incubation with catS (Fig.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…The half-maximal reactions occurred around 1–2 nM nid-1, in agreement with the apparent dissociation constant, Kd [34]. Previous studies showed that human nid-1 had weaker affinities for collagen IV and perlecan than for laminin [11]. We next examined the binding of a mixture of nid-1 fragments produced by incubation with catS (Fig.…”
Section: Resultssupporting
confidence: 77%
“…It has to be noticed that the 150 kDa form of unprocessed nid-1 is known to be highly susceptible to endogeneous proteolysis (particularly within its N-terminal domain G1) during pre-extraction tissue and that N-terminally cleaved form of ∼90 kDa nid-1 was already described in other murine BM tissues extracts. However, G2 and G3 domains are conserved and still bind to BM partners (type IV collagen, laminins, perlecan, fibulins) [11]. Experiments were also performed with an isolated nidogen/laminin complex from EHS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both entactin isoforms are glycosylated proteins that consist of three globular domains (G1 to G3) connected by a flexible link and a rod (Fox et al, 1991;Mayer et al, 1995;Kimura et al, 1998;Kohfeldt et al, 1998).…”
Section: Introductionmentioning
confidence: 99%